Pengembangan Buku Siswa dan Buku Petunjuk Guru Matematika Berorientasi Pemecahan Masalah dengan Setting 5E - Sumadi Sumadi; Margaretha N. Inna (Pusat Pengembangan dan Pemberdayaan Pendidik dan Tenaga Kependidikan Matematika, 2019)
This study aims to develop and produce student book and teacher manual book in teaching and learning for the topic of Problem Solving-oriented Linear Equation System of Two Variables with 5E setting. This is a development research on problem solving-oriented learning models with 5E settings. The research utilises supporting learning devices that includes student books, teacher manuals and lesson plans. The process of developing student books and teacher manuals refers to the Plom model of developing procedure. Subject of this study is 36 students of grade X Vocational School 1 Denpasar. The student book which was developed is valid with a score of 3, while the teacher's manual score is 3.8 with a quite valid category. In the first practicallity test, the average score of student books and teacher manuals was 3.1, while in the second field test the score was 3.2, it is in the practical categories.The effectiveness of student books and teacher manuals in field trial 1 reached a score of 78.92 (good), while in the field trial 2 the score was 86.07 (very good). This fact shows that the problem solving- oriented student books and teacher manuals with the 5E setting are worthy to be used as learning sources for vocational mathematics, because they meet the criteria for validity, practicality, and effectiveness.